Plastic bronchitis due to adenoviral infection: a case report - Zhang, Fei Zhou (BMC Pediatr, 2020)
BACKGROUND: Plastic bronchitis (PB) frequently occurs as a serious postoperative complication of the Fontan procedure. The definitive causes of PB are unknown. CASE PRESENTATION: Herein, we report a pediatric case of PB secondary to adenoviral infection. A 4-year-old girl was admitted to the general pediatric ward for cough since 2 weeks and fever since 11 days. Consolidated lesions were noted in the right upper and both lower lung lobes. Extracorporeal membrane oxygenation was performed because the patient’s respiratory failure remained unalleviated despite the use of a ventilator. Bronchial dendritic casts were extracted using flexible bronchoscopy, and the patient’s breathing improved. Pathological examination of the dendritic cast confirmed the diagnosis of type I PB. The exfoliated cells of sputum and cells from bronchoalveolar lavage fluid were positive for adenoviral antigen. Human adenovirus 7 was detected by next-generation sequencing of the bronchoalveolar lavage fluid. The patient recovered and was discharged 39 days after admission without recurrence of cough or wheezing. CONCLUSIONS: PB due to human adenovirus 7 infection should be considered in children with persistent respiratory failure. Flexible bronchoscopy should be performed early to confirm diagnosis and to remove any airway obstruction.